Total antioxidant levels of saliva in children related to caries, age, and gender - O. TULUNOGLU, S. DEMIRTAS, & I. TULUNOGLU (Paediatric Dentistry, 2006)
The purpose of this study was to evaluate the relationship between the physicochemical properties of saliva such as flow rate, buffering capacity, pH, calcium level, total protein, total antioxidant status, and dental caries, age, and gender.